Callosal microstructure affects the timing of electrophysiological left-right differences - Friedrich, Patrick; Ocklenburg, Sebastian; Heins, Nina; Schlüter, Caroline; Fraenz, Christoph; Beste, Christian; Güntürkün, Onur; Genç, Erhan (NeuroImage, 2017)
The neural architecture of the corpus callosum shows pronounced inter-individual differences. These differences are thought to affect timing of interhemispheric interactions and, in turn, functional hemispheric asymmetries. The present study aimed at elucidating the neuronal mechanisms underlying this relationship. To this end, we used a combined DTI and EEG study design. In 103 right-handed and healthy adult participants, we determined the microstructural integrity of the posterior third of the corpus callosum and examined in how far this microstructural integrity was related to between-hemisphere timing differences in neurophysiological correlates of attentional processes in the dichotic listening task. The results show that microstructural integrity of the posterior callosal third correlated with attentional timing differences in a verbal dichotic listening condition but not in a noise control condition. Hence, this association between callosal microstructure and between-hemisphere timing differences is specific for stimuli, which trigger hemispheric bottom-up processing in an asymmetric fashion. Specifically, higher microstructural integrity was associated with decreased left-right differences in the latency of the N1 event-related potential component and hence more symmetric processing of dichotic stimuli between the two hemispheres. Our data suggest that microstructure of the posterior callosal third affects functional hemispheric asymmetries by modulating the timing of interhemispheric interactions.
Keywords: EEG; Humans; Functional Laterality; corpus callosum; DTI; Female; mladý dospělý; dospělí; lidé; elektroencefalografie; zobrazování difuzních tenzorů; Adult; ženské pohlaví; funkční lateralita; Diffusion Tensor Imaging; Male; Adolescent; Interhemispheric interaction; Young Adult; Electroencephalography; Corpus callosum; mužské pohlaví; Hemispheric asymmetries; Corpus Callosum; mladiství